1993
DOI: 10.1002/jnr.490340212
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the minimal epitope of monoclonal antibody Tau‐1 depends upon the presence of a phosphate group but not its location

Abstract: The major constituent of the paired helical filaments (PHFs) of Alzheimer's disease is the abnormally phosphorylated form of the microtubule-associated protein, tau. Monoclonal antibody (mAb) Tau-1 is used extensively to stain normal human tau, and tau isolated from the brains of Alzheimer's disease patients after dephosphorylation. We used a panel of 6 synthetic peptides to localize the minimal epitope of Tau-1 between amino acids 192-204. All 4 serine residues within this fragment were later phosphorylated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(111 citation statements)
references
References 31 publications
6
105
0
Order By: Relevance
“…The conformation-modifying effect of the aspartic-acidbond isomerization is similar to that of carbohydrate incorporation into synthetic peptides and clearly different from that of phosphorylation. While phosphorylation is heavily sequence dependent and clear-cut conclusions are difficult to draw (Lang et al, 1992;Szendrei et al, 1993), we showed earlier that internal glycosylation of synthetic peptides generally breaks helices, and /I turns are formed after glycosyla- tion of T-cell epitopic a-helical peptides (Otvos et al, 1991). Similarly to the P-aspartyl peptides, external glycosylation did not affect the secondary structure of the peptides .…”
Section: Discussionmentioning
confidence: 99%
“…The conformation-modifying effect of the aspartic-acidbond isomerization is similar to that of carbohydrate incorporation into synthetic peptides and clearly different from that of phosphorylation. While phosphorylation is heavily sequence dependent and clear-cut conclusions are difficult to draw (Lang et al, 1992;Szendrei et al, 1993), we showed earlier that internal glycosylation of synthetic peptides generally breaks helices, and /I turns are formed after glycosyla- tion of T-cell epitopic a-helical peptides (Otvos et al, 1991). Similarly to the P-aspartyl peptides, external glycosylation did not affect the secondary structure of the peptides .…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein from each sample were diluted in 2ϫ SDS stop buffer (0.5 M Tris-Cl, pH 6.8, 10% SDS, 10 mM EGTA, 10 mM EDTA, 25 mM dithiothreitol, 10% glycerol, 0.01% bromphenol blue), incubated in a boiling water bath for 5 min, electrophoresed on 10% SDS-polyacrylamide gels, transferred to nitrocellulose membrane, and probed with the indicated antibodies. The tau antibodies used in this study were Tau5 and 5A6 (Tau5 from Dr. L. Binder), which are phosphoindependent tau antibodies (37, 38), Tau-1 (from Dr. L. Binder), which recognizes tau only when Ser-195, Ser-198, Ser-199, Ser-202, and Thr-205 (numbered according to the longest human brain tau isoform (10)) are not phosphorylated (39,40), PHF-1 (from Dr. P. Davies), which recognizes tau phosphorylated at Ser-396/404 (41), and AT180 (Endogen), which recognizes tau phosphorylated at Thr-231 (42,43). An antibody to ␤-actin (Chemicon) was also used.…”
Section: Methodsmentioning
confidence: 99%
“…Tau-5 (from Dr. L. Binder) recognizes tau epitopes independent of their phosphorylation state (24). Tau-1 (from Dr. L. Binder) recognizes tau dephosphorylated at residues 189 -207 (25,26). 12E8 (from Dr. P. Seubert) recognizes Ser 262/356 -phosphorylated tau (27).…”
Section: Methodsmentioning
confidence: 99%